Laparoscopic management of early stage primary fallopian tube carcinoma (Indian Journal of Case Reports, 2019)
Primary fallopian tube cancer (PFTC) is a rare malignancy with an incidence of 0.14-1.8% of all genital malignancies. Presentations of fallopian tube cancer are mostly nonspecific and include abdominal pain, profuse watery or serosanguinous discharge. Here, we present the case of a 51-year-old patient with FIGO stage 1A PFTC. It was diagnosed as hematosalpinx intraoperatively, during total laparoscopic hysterectomy and diagnosed as PFTC on histopathology. Further management was by laparoscopic staging. A high index of suspicion is needed in peri and postmenopausal women who present with unexplained uterine bleeding, profuse discharge, pelvic pain, adnexal mass or abnormal pap smear.